Bloqueio retrobulbar com levobupivacaína e lidocaína em gatos - Xavier, Gustavo Delfino (2014)
The objective of this study was to assess the effect of retrobulbar anesthesia in cats with levobupivacaine chloride 0.5% and lidocaine chloride 2% without vasoconstrictor. Fourteen cats were divided into two groups and underwent preanesthetic medication with acepromazine maleate and propofol. Retrobulbar block was performed in the medial corner of the eyelids of the right eyeball with levobupivacaine hydrochloride (Group I) and lidocaine (Group II) without vasoconstrictor. We evaluated the M0 moments i.e. six hours prior to PAM, M1:15 minutes after PAM, when it was taken the anesthetic, as well as the periods M2: 15, M3: 30, M4: M5: 45 and M6: 60 minutes after the anesthetic block. The duration of block with lidocaine was 50 minutes, and 65 minutes with levobupivacaine without change in systolic blood pressure. Anesthetic promoted block of the corneal and the oculocephalic reflexes, being that the loss of sensibility and return of the corneal reflexes were faster with the levobupivacaine than with the lidocaine. No changes in the coloration of the eyelid and bulbar conjunctivae and decentralization of the globe were noted. Anesthetics caused retrobulbar anesthesia in cats, being that 0.5% levobupivacaine promotes appearance of rash in the bulbar and the eyelid conjunctivae, greater reduction in tear production and increased intraocular pressure. Anesthetics are not able to restrict the palpebral reflexes, but they may be used for intraocular surgery.